Human Resource Management in Selected District Hospitals of Bangladesh- A Cross Sectional Study (Update Dental College Journal, 2018)
Human resource management (HRM) is fundamental of any organization because of its utility. A cross-sectional was conducted from January to December, 2016 in two district hospitals named Gen- eral Hospital, Munshiganj and 100 Bedded District Hospital, Narsingdi with the objective to assess the status of HRM. Purposively 144 hospital staffs were selected and interviewed by using semi-struc- tured questionnaire and record review. The collected data were processed and analyzed meticulously with the help of SPSS (Version 21) software on the basis of different variables. The study revealed that the mean age was 36.6 ± 1.8 years, 71.5 % were clinical and nursing personnel, other category of respondents were support services and other personnel (22.2%), administrative personnel (6.3  %).Most (96.5 %) of the respondents were recruited by Government, after recruitment 52.1% hospital staffs mentioned scope of training facilities either work-based or instruction based exists in workplace,  63.9 % needed to be trained, 80.6% wished further career plan. Working environment found friendly by 39.6 % hospital staffs, where as average found by 50.0%. The recommendations for further improvement of HRM of their workplace was to increase training facilities by 31.9%, other recommen- dations were to increase manpower, improvement of monitoring and supervision. From this study some effort in the training, increase of manpower , performance appraisal can ensure better quality of service at district hospitals.Update Dent. Coll. j: 2017; 7 (2): 28-32